KIMONO: SARANA EKSPRESI KECINTAAN ORANG JEPANG TERHADAP ALAM - , KIRANA CITTALAKSMI; , Sri Pangastoeti, SS., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research studies the traditional Japanese attire, the kimono. The purpose of this research is to know the things on kimono which reflect the relationship with nature and the reason why kimono accentuate those things associated with nature in the model, motifs, colors, and its usage. This study is a research with qualitative data obtained through literature review. The results of this research show the things in kimono that depict relationship with the nature. Firstly, kimono model, along with the koromogae tradition indicates that the Japanese people always try to live as aligned with the nature. Secondly, the combination of colours and the motives found in a kimono not only demonstrates sensitivity and deep response to the surrounding nature, but also shows the effort to bring it closer to the real life. To conclude, those aspects in kimono represent the Japaneseâs appreciation towards nature. Keywords: kimono, expression, the Japaneseâs appreciation towards nature.